2010
DOI: 10.1159/000319594
|View full text |Cite
|
Sign up to set email alerts
|

Global Evolutionary Trend of the Prevalence of Primary Glomerulonephritis over the Past Three Decades

Abstract: Objective: The prevalence of primary glomerulonephritis in Singapore is compared with that of 28 other countries to review changing trends in the evolution of primary glomerulonephritis in Asia and other countries. Method: 2,586 renal biopsies in Singapore over the past 3 decades were reviewed and compared with data from 28 other countries. Results: In the 1st decade most Asian countries have mesangial proliferative glomerulonephritis as the most common form of primary glomerulonephritis, and in the 3rd decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 54 publications
2
56
1
1
Order By: Relevance
“…1,2 The prevalence as well as the prognosis of IgAN shows geographic and ethnic variation. It is reported to be significantly more common in Asians especially in Japan, Singapore, and China [3][4][5][6] and Chinese patients have been shown to have poorer prognosis compared to their Western counterparts. 6 The prevalence of IgAN in India 7-10 is reported to be 4.5-16% of all patients with biopsy verified glomerular disease, and it is considered to be a severe disease with poor outcome.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The prevalence as well as the prognosis of IgAN shows geographic and ethnic variation. It is reported to be significantly more common in Asians especially in Japan, Singapore, and China [3][4][5][6] and Chinese patients have been shown to have poorer prognosis compared to their Western counterparts. 6 The prevalence of IgAN in India 7-10 is reported to be 4.5-16% of all patients with biopsy verified glomerular disease, and it is considered to be a severe disease with poor outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Mundi I etal and Mannan R et al 10,13 demonstrated FSGS, MN and minimal change disease(MCD) being the commonest form of PGN in India. Data from Singapore and other countries also showed that the prevalence of FSGS and MN have become increased in recent time 1 This may be related to increasing number of patients with obesity, DM and smoking habits, a pattern representing the rising affluence in these countries where FSGS represents the changing life style of fast food and unhealthy diets predisposing to disease like obesity and DM. In our study though many of our cases were diabetic but there average body built and life style do not yet match with that of the affluent society.…”
Section: Primary Gnmentioning
confidence: 98%
“…The pattern of glomerulonephritis (GN) varies widely from country to country, reflecting the possible effects of socio-economic, genetic and environmental factors. 1 The disease spectrum is also been changing over the last few decades. 1 IgA nephropathy is the commonest primary glomerular disease from east Asia, as well as in white Europeans and Americans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of glomerulonephritis (GN) varies widely from country to country, reflecting the possible effects of socio-economic, genetic and environmental factors. 1 The disease spectrum has also been changing over the last few decades. 1 IgA nephropathy is the common primary glomerular disease from East Asia, as well as in white Europeans and American.…”
Section: Introductionmentioning
confidence: 99%